2015
DOI: 10.1371/journal.pone.0131173
|View full text |Cite
|
Sign up to set email alerts
|

BcMF26a and BcMF26b Are Duplicated Polygalacturonase Genes with Divergent Expression Patterns and Functions in Pollen Development and Pollen Tube Formation in Brassica campestris

Abstract: Polygalacturonase (PG) is one of the cell wall hydrolytic enzymes involving in pectin degradation. A comparison of two highly conserved duplicated PG genes, namely, Brassica campestris Male Fertility 26a (BcMF26a) and BcMF26b, revealed the different features of their expression patterns and functions. We found that these two genes were orthologous genes of At4g33440, and they originated from a chromosomal segmental duplication. Although structurally similar, their regulatory and intron sequences largely diverg… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
16
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
9
1

Relationship

2
8

Authors

Journals

citations
Cited by 26 publications
(18 citation statements)
references
References 66 publications
1
16
0
Order By: Relevance
“…At the transcription level, the combination of cis-acting elements and transcription factors in the promoter region is involved in the regulation of gene expression. For example, two duplicated PG genes, BcMF26a and BcMF26b , in B. rapa , with amino acid sequences, had 92.19% similarity and showed a divergent expression and function, which may be responsible for their promoters having a very large divergence (63.20% similarity) [ 44 ]. In our study, the cis-elements in BoPGs’ promoter sequences were identified and analyzed.…”
Section: Discussionmentioning
confidence: 99%
“…At the transcription level, the combination of cis-acting elements and transcription factors in the promoter region is involved in the regulation of gene expression. For example, two duplicated PG genes, BcMF26a and BcMF26b , in B. rapa , with amino acid sequences, had 92.19% similarity and showed a divergent expression and function, which may be responsible for their promoters having a very large divergence (63.20% similarity) [ 44 ]. In our study, the cis-elements in BoPGs’ promoter sequences were identified and analyzed.…”
Section: Discussionmentioning
confidence: 99%
“…Possibly, the thickened intine in atsec23a is responsible for the impaired pollen germination rate by increasing the required pressure for pollen germination. In Brassica campestris , knockdown of BcMF8 (putative arabinogalactan protein gene) and double knockdown of BcMF26a and BcMF26b (polygalacturonase genes) causes reduced pollen germination and retarded pollen tube growth as a result of remarkable thickening of the intine ( Lin et al , 2014 ; Lyu et al , 2015 ). In atsec23a , AtSEC23D had the main function in pollen development.…”
Section: Discussionmentioning
confidence: 99%
“…PG is one of the major enzymes involved in pectin disassembly by biochemically catalyzing the hydrolytic cleavage of a (1–4) galacturonan [ 37 38 ]. Pectin is one of the major components of the primary cell wall, whose disassembling leads to cell wall separation [ 39 40 ].…”
Section: Discussionmentioning
confidence: 99%